(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract: The conquest of Islam for Spain was the beginning of a new era, and a great development began in its public life and in its social systems. The era of the conquest was afflicted and exhausted by injustice and abuse, and the fees of slavery and servitude were imposed on it, and all freedoms and sanctuaries were permitted from it, so Islam came to eliminate all of that, and to bear the blessings of justice Freedom and equality for all people, and to give everyone his right, to suppress oppression and injustice, to achieve prosperity and bliss, and to spread justice and equality in all parts of Spain and the surrounding areas. The importance of the topic: It deals with one of the pages of the Islamic presence in Europe, specifically in Andalusia, and despite all that the Muslim Arabs have provided for eight centuries, the Christians of Spain and Europe in general, however, refuse to deny that and start aggressive campaigns to expel Muslims from Spain and cross to the other bank in terms of They crossed. And the reason for choosing the topic: is to shed light on the terrorism that was practiced against Muslims and their presence in Andalusia, which has become, thanks to the Muslim Arabs, a Qibla and beacon of science, culture and religious tolerance. The research has been divided into an introduction, three chapters and a conclusion in which the most important conclusions reached by the researcher, and a list of sources and references arranged according to the alphabetical letter of the Arabic letter. In the first topic, we reviewed the movement of recovery and economic attrition, the second topic: military attrition, and the third topic: the missionary method. Upon completing his research, the researcher concluded the following: The standing of Zaragoza (the eastern gate of Andalusia) in the face of the Crusader challenge coming from France and the northern Spanish kingdoms after the fall of the Umayyad Caliphate (442 AH / 1031 AD) and the emergence of the era of Taifa kings, when the Banu Hood took over its rule (in 40 AH / 1038 AD) and ended with its fall at the hands of the Almoravids (in 503 AH). /1109 AD). The research begins by talking about the change in the balance of power in Spain in favor of the Spanish kingdoms, which used two methods to destroy the opponent: economic attrition and military attack, which came to fruition by bringing down Prechter (456 AH / 1064 AD) one of the most important cities of the administration of Zaragoza by a campaign that came out of France under the direction of the Pope, which confirms its Crusader reality . The research goes on to talk about the Islamic reactions to the fall of Brecher and the Bani Hood sought to retrieve it and declare jihad throughout Andalusia, but this did not stop the Spanish advance and their tendency to besiege Zaragoza itself twice, but they were forced to withdraw due to the crossing of the Almoravids from Morocco and began to focus their campaigns supported by France against other cities such as Wachqa and Tatila And they managed to bring them down. The research ends with a talk about the missionary method in which the Christian Front attempts against the Muslims of Andalusia. Letters addressed to the rulers of Zaragoza, Ahmed bin Hood, began calling him to convert. The research stopped at one of these messages and the controversy it raised among scholars, and at the end cited its text and the text of the answer of the Andalusian jurist, Abu Al-Walid Al-Baji to it. The researcher has used many sources and references that dealt with the subject and referred to in the list of sources and references.